2021
DOI: 10.1002/iid3.563
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled clinical trial on efficacy and safety of anakinra in patients with severe COVID‐19

Abstract: Introduction Hyperinflammatory state has a role in the pathogenesis of COVID‐19. Anakinra could reduce inflammation and help to combat the condition. In this study, we aimed to assess the safety and efficacy of anakinra (PerkinRA®) in severe COVID‐19. Method The study was an open‐label, randomized, controlled trial conducted in Imam Hossein Medical Center from May to July 2020. Patients with a confirmed diagnosis of COVID‐19 were included in this study. We administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 18 publications
0
25
0
6
Order By: Relevance
“…With a half-life of 26 days, canakinumab is a preferred treatment option and has been approved for CAPS, juvenile idiopathic arthritis, rare periodic fever syndromes, and adult-onset Still's disease (AOSD) (Curran, 2012;Orrock and Ilowite, 2016;Malcova et al, 2020;Sfriso et al, 2020). In addition, a number of clinical trials have recently investigated anakinra and canakinumab as a therapeutic treatment for patients with COVID-19 (Kooistra et al, 2020;Landi et al, 2020;Kyriazopoulou et al, 2021;Kharazmi et al, 2022). These therapies have proven to be safe and effective in treating inflammation-driven diseases, however, some issues remain.…”
Section: Anakinra (Kineret ) Rilonacept (Arcalyst ) and Canakinumab (...mentioning
confidence: 99%
“…With a half-life of 26 days, canakinumab is a preferred treatment option and has been approved for CAPS, juvenile idiopathic arthritis, rare periodic fever syndromes, and adult-onset Still's disease (AOSD) (Curran, 2012;Orrock and Ilowite, 2016;Malcova et al, 2020;Sfriso et al, 2020). In addition, a number of clinical trials have recently investigated anakinra and canakinumab as a therapeutic treatment for patients with COVID-19 (Kooistra et al, 2020;Landi et al, 2020;Kyriazopoulou et al, 2021;Kharazmi et al, 2022). These therapies have proven to be safe and effective in treating inflammation-driven diseases, however, some issues remain.…”
Section: Anakinra (Kineret ) Rilonacept (Arcalyst ) and Canakinumab (...mentioning
confidence: 99%
“…According to adult studies, anakinra reduces the need for mechanical ventilation, length of stay in the hospital and intensive care unit, and mortality in patients with COVID-19 ( 19 , 20 ). But, unfortunately, despite intensive treatment, the mortality rate of MIS-C is reported to range between 1.2 and 1.7% ( 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…The median resolution day of the fever was 3 (1-10) days after anakinra treatment. The lymphocyte counts, BNP, CRP, and D-dimer values of the patients became normal on the median day of 5 (1-18), 8.5 (5-53), 10 (1-33), and 11.5 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), respectively. The pattern of improvement in EF…”
Section: Outcome and Safetymentioning
confidence: 94%
“…Authors found that only patients with phenotype C (with a higher inflammatory status) benefit from corticosteroid therapy consistent with the study by Chen et al 7 It has also been shown that immunomodulatory drugs (tocilizumab, sarilumab (IL-6 inhibitors) and anakinra (interleukin-1 inhibitor)) are associated with the reduced need for IMV, improve survival in critically-ill COVID-19 patients; whereas in patients with mild COVID-19 pneumonia, immunomodulatory drugs do not improve outcomes. 51,52 Observational studies showed encouraging results on the use of IL-6 inhibitors in severe COVID-19 cases and a recent meta-analysis including 16 observational studies noted a decreased risk of death associated with the use of tocilizumab (OR 0.57 [95% CI 0.36-0.92]) compared to standard care. 53 In another prospective observational study from Italy, 56 severe COVID-19 cases with elevated inflammatory markers were analyzed for efficacy of sarilumab.…”
Section: Discussionmentioning
confidence: 99%